Transformasi Bentuk-Representasi dan Performativitas Gender dalam Seni Tradisi Topeng Ireng - Kiswanto Kiswanto (Universitas Gadjah Mada, 2017)
Transformation of Topeng Ireng Traditional Arts into Topeng Ireng Gugur Gunung of Duta Seni Pelajar Boyolali in this paper was discourse through some theory perspective developed by Maruška Svašek, Judith Butler, and some related writers. Transformation is characterized by changes in objects that transit within the location or the new owner, that is the material or forms of traditional art patterns of Topeng Ireng that transit as the initial idea of the creator. The object changed because in the process has been adapted to the concept of Gugur Gunung, which then processed, combined, developed, transformed into new works of art. Transformation is also marked by transitions related to the shifting meaning, value, and benefi ts of the object. The changes show a transition in several aspects, including content represented through art forms and performativity of gender.